REVEALED: Secret Ingredients in the Chairperson’s Recipe for Assessment - Ryan Chung; Frederick Burrack; Kelva Hunger (Academic Chairpersons Conference Proceedings, 2020)
Academic chairpersons often experience frustration or lack of support when helping faculty/staff develop and administer assessment processes. This session will provide information and strategies on how to effectively guide program assessment processes.
Keywords: Assessment; Collaboration; Assessment Strategies; Supporting Faculty; Accountability